Hedging Efficiency of Energy Commodities between Indian and American Commodity Exchanges: Constant and Time-Varying Approaches - Rajesh, R.; Nandini, A. Satya (International Journal of Energy Economics and Policy, 2023)
This research paper investigates the hedging efficiency between spot and future prices of crude oil and natural gas commodities in the energy category of the commodity market. The study focuses on two major commodity exchanges, the Multi Commodity Exchange of India (MCX) and the New York Mercantile Exchange (NYMEX), which serve as the global benchmarking commodity market. Various econometric models have been incorporated to measure constant and time-varying hedging efficiency, we analyze the potential of futures contracts in mitigating price risks in these markets. The results indicate significant and consistent hedge ratios for both crude oil and natural gas in both the MCX and NYMEX markets. Moreover, the MGARCH model, which assesses hedging that varies over time, demonstrates the ability to adjust hedging positions based on market changes. Johansen's co-integration test endorses the presence of enduring connections between spot and future prices in both exchanges. Traders and investors can effectively use futures contracts to mitigate price risks in energy commodity markets, ensuring more dependable financial outcomes amid price fluctuations. Additionally, policymakers can utilize these research findings to promote the adoption of futures contracts, make well-informed choices, manage risks effectively, and enhance the overall efficiency and stability of energy commodity markets.